SUMO modification system facilitates the exchange of histone variant H2A.Z-2 at DNA damage sites - Fukuto, Atsuhiko (Nucleus, 2017)
Histone exchange and histone post-translational modifications play important roles in the regulation of DNA metabolism, by re-organizing the chromatin configuration. We previously demonstrated that the histone variant H2A.Z-2 is rapidly exchanged at damaged sites after DNA double strand break induction in human cells. In yeast, the small ubiquitin-like modifier (SUMO) modification of H2A.Z is involved in the DNA damage response. However, whether the SUMO modification regulates the exchange of human H2A.Z-2 at DNA damage sites remains unclear. Here, we show that H2A.Z-2 is SUMOylated in a damage-dependent manner, and the SUMOylation of H2A.Z-2 is suppressed by the depletion of the SUMO E3 ligase, PIAS4. Moreover, PIAS4 depletion represses the incorporation and eviction of H2A.Z-2 at damaged sites. These findings demonstrate that the PIAS4-mediated SUMOylation regulates the exchange of H2A.Z-2 at DNA damage sites.